Human Resources Development and Utilization: The Challenges in Education Delivery - Musa, C. N.; Musa, R. (International Journal of Educational Management, 2022)
The thesis of this paper is that the professional development and utilization of human resources requires the cooperative working together of both the education system and the various segments of the economy, especially the job market. It is through well coordinated and organized educational institutions that the relevant knowledge and skills are professionally appropriated for the development of the human resources who in turn ply these skills into the respective development sectors of the economy. The paper points out that the Nigerian education system is not delivering adequately as it should in the development equation because of the over four decades of decay and deficiencies in infrastructure, insecurity of lives and property, huge urban unemployment, total development failures at the lower levels of government and acute educational crises in terms of opportunities in the country. The paper also observed the major challenges in the area of the dearth of accurate educational data, the problem of funding, the poor quality of the products of the educational system and their employablility. The paper concludes on the note that the education system and other sectors of the economic development system have to work together in order to avoid the glaring mismatch between the absorbing capacity of the development system and the education outputs.